Prognostic relevance of mitral and tricuspid regurgitation in patients with severe aortic stenosis. (1st March 2018) - Zilberszac, Robert; Gleiss, Andreas; Binder, Thomas; Laufer, Günther; Grimm, Michael; Gabriel, Harald; Maurer, Gerald; Rosenhek, Raphael
Abstract: Aims: Although concomitant mitral regurgitation (MR) and tricuspid regurgitation (TR) are frequently present in patients with aortic stenosis (AS), outcome data are scarce and treatment strategies are controversial. The aim of the present study was to assess the presentation and outcome of patients with AS and coexisting MR and TR. Methods and results: Eighty-nine consecutive patients with severe AS and at least moderate MR (72 functional and 17 degenerative) were included and followed. Seventy-five patients were symptomatic at presentation. Sixty of these had severe symptoms (New York Heart Association class ≥3). Nine additional patients had an indication for valve procedures during follow-up. However, 35 patients were managed conservatively. Isolated aortic valve intervention was performed in 29 patients (22 valve replacement and 7 transcatheter aortic valve replacement) and concomitant mitral valve surgery in 20 patients. For the assessment of outcome, overall survival (i.e. time from study entry to death from any cause) was assessed: adjusted survival was significantly higher for patients undergoing any valve procedure as compared with patients managed conservatively ( P = 0.032). Surgical treatment of severe concomitant MR was associated with improved survival in an unadjusted population but did not reach statistical significance after propensity adjustment. 14 of 36 patients who had concomittant moderate-to-severe tricuspid regurgitation (TR) underwent surgery of which 7 (50 %) died within 3 months postoperatively. On the other hand, only 1 of 35 (3%) with no or mild TR undergoing surgery died within 3 months post-operatively ( P < 0.001). Conclusion: Presence of MR in patients with severe AS characterizes a high-risk population. Timely aortic valve intervention confers a survival benefit and concomitant mitral valve surgery should be considered according to operative risk. The additional presence of significant TR is associated with dismal outcomes, regardless of the treatment strategy.